Microstructure Evolution of Nickel Strike Plating Layer by Electrochemical Deposition and Heat Treatment - Im, Byoungyong; Choi, Jiwon; Kim, Ki Buem; Kim, Dae-Guen (Archives of Metallurgy and Materials, 2026)
Nickel strike layers were electrodeposited on stainless steel from a NiCl2-HCl bath, and the effects of applied potential, deposition time, and post-plating heat treatment were investigated. Chronoamperometry showed that cathodic current density increased and current fluctuations became more pronounced at more negative potentials, indicating intensified hydrogen evolution. Surface images revealed needle-like morphology at less negative potentials, whereas non-uniform deposition with incomplete coating regions appeared at –1.8 V due to competition from hydrogen evolution. Heat treatment transformed the surface into polygonal grains and promoted grain coarsening. Texture analyses indicated increased average grain size and decreased local misorientation, suggesting microstructural recovery and relaxation of residual/internal stress.